Long-Term Follow-Up of a Donor versus No-Donor Comparison in Patients with Multiple Myeloma in First Relapse after Failing Autologous Transplantation - Patriarca, Francesca; Bruno, Benedetto; Einsele, Hermann; Spina, Francesco; Giaccone, Luisa; Montefusco, Vittorio; Isola, Miriam; Nozzoli, Chiara; Nozza, Andrea; Morabito, Fortunato; Corradini, Paolo; Fanin, Renato (Biology of Blood and Marrow Transplantation, 2018)
We report the long-term clinical outcomes of a retrospective multicenter study that enrolled 169 patients with multiple myeloma (MM) in first relapse after failing autologous stem cell transplantation (SCT). After HLA typing at relapse, 79 patients with a suitable donor, 72 (91%) of whom eventually underwent salvage allogeneic SCT (allo-SCT), were compared with 90 patients without a donor who were treated with multiple lines of salvage treatment with bortezomib and/or immunomodulatory agents. At a median follow-up of 30 months (range, 2-180 months) for all patients and 110 months (range, 38-180 months) for surviving patients, 7-year progression-free survival (PFS) was 18% in the donor group and 0% in the no-donor group (hazard ratio [HR], 2.495; 95% confidence interval [CI], 1.770-3.517; P <.0001). Seven-year overall survival (OS) was 31% in the donor group and 9% in the no-donor group (HR, 1.835; 95% CI, 1.306-2.577; P <.0001). By multivariate analysis, chemosensitivity to salvage treatments and presence of a suitable donor were significantly associated with better PFS and OS. The long-term follow-up of this study confirms the significant PFS benefit and provides new evidence of an OS advantage for patients with MM who have a suitable donor and undergo allo-SCT. Allo-SCT should be considered as a treatment option in young relapsed patients with high-risk disease features after first-line treatment.
CRIS-Team Scopus Importer:2023-03-23
Keywords: Allogeneic stem cell transplantation; Long-term follow-up; Multiple myeloma